Guidance and Counseling Teachers Strategies In Handling Late Students - Anandaputriani, Melda; Haniati, Umi (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2025)
Discipline is an attitude or behavior that students must have at school. Students should obey the rules that apply at school, especially discipline regarding arrival times. However, in reality there are still many students who are late coming to school for various reasons. Even though it is clear that the rule at school is that students arrive at 07.00 WIB. This also happens at MTs N 1 Banyumas where most of the students who attend school there also live in Islamic boarding schools and orphanages around the school, so they have a greater influence for coming late to school. This is where the role and strategies of guidance and counseling teachers are needed to discipline students who are late coming to school. Guidance and counseling teachers at MTs N 1 Banyumas provide punishment in the form of religious conditioning at school, because guidance and counseling teachers there strictly avoid physical punishment to their students. Apart from that, guidance and counseling teachers also provide individual counseling and calling parents to students who have been late to school 3 times. This research uses a descriptive qualitative approach. Where researchers take data from sources. and get involved directly in the field.